Impact of climate change on northern vegetation limits and forest tree wind seed dynamics from the Last Glacial Maximum to presen - Krassimir D. Naydenov; Michel K. Naydenov; Alexander Alexandrov; Todor Gurov; Georgi Hinkov; Sofiya Ivanovska; Veselka Gyuleva; Silvi-Maria Gurova; Biljana Nikolic; Makech Balakumar (Silva Balcanica, 2025)
Seeds interact with climate and soil factors during their dispersal, determining the natural distribution areas of species and influencing their geographic fluctuations. These fundamental roles have a significant impact on species evolution and population genetic robustness at the perpetual abiotic change of the ecological conditions. The study investigates the distribution of ice during the Last Glacial Maximum (LGM) and its effect on the tree line in forested areas.We compared the hypothesis of the LGM’s permanent ice extent and its impact on vegetation limits with the speed of forest tree seed dispersal. Our analysis suggests that the permanent ice cover during the LGM was likely more restricted and fragmented than initially believed. The presence of multiple micro refugia along the current tree line was located no more than 150 km from the present-day northern tree distribution. This observation does not contradict the extent of the ice sheet in the Northern Hemisphere during the Last Glacial Maximum (LGM).